Expansion of CD4+ cytotoxic T lymphocytes with specific gene expression patterns may contribute to suppression of tumor immunity in oral squamous cell carcinoma: single-cell analysis and in vitro experiments - Chen, Hu; Sameshima, Junsei; Yokomizo, Shiho; Sueyoshi, Tomoki; Nagano, Haruki; Miyahara, Yuka; Sakamoto, Taiki; Fujii, Shinsuke; Kiyoshima, Tamotsu; Guy, Thomas; Nakamura, Seiji; Moriyama, Masafumi; et al. (Frontiers in Immunology, 2023)
Background: Cancer immunotherapy targeting CD8 + T cells has made remarkable progress, even for oral squamous cell carcinoma (OSCC), a heterogeneous epithelial tumor without a substantial increase in the overall survival rate over the past decade. However, the therapeutic effects remain limited due to therapy resistance. Thus, a more comprehensive understanding of the roles of CD4 + T cells and B cells is crucial for more robust development of cancer immunotherapy.In this study, we examined immune responses and effector functions of CD4 + T cells, CD8 + T cells and B cells infiltrating in OSCC lesions using single-cell RNA sequencing analysis, T cell receptor (TCR) and B cell receptor (BCR) repertoire sequencing analysis, and multi-color immunofluorescence staining. Finally, two Kaplan-Meier curves and several Cox proportional hazards models were constructed for the survival analysis.We observed expansion of CD4 + cytotoxic T lymphocytes (CTLs) expressing granzymes, which are reported to induce cell apoptosis, with a unique gene expression patterns.CD4 + CTLs also expressed CXCL13, which is a B cell chemoattractant. Cell-cell communication analysis and multi-color immunofluorescence staining demonstrated potential interactions between CD4 + CTLs and B cells, particularly IgD -CD27 -double negative (DN) B cells. Expansion of CD4 + CTLs, DN B cells, and their contacts has been reported in T and B cell-activated diseases, including IgG4-related disease and COVID-19. Notably, we observed upregulation of several inhibitory receptor genes including CTLA-4 in CD4 + CTLs, which 3 possibly dampened T and B cell activity. We next demonstrated comprehensive delineation of the potential for CD8 + T cell differentiation towards dysfunctional states. Furthermore, prognostic analysis revealed unfavorable outcomes of patients with a high proportion of CD4 + CTLs in OSCC lesions.Our study provides a dynamic landscape of lymphocytes and demonstrates a systemic investigation of CD4 + CTL effects infiltrating into OSCC lesions, which may share some pathogenesis reported in severe T and B cell-activated diseases such as autoimmune and infectious diseases.